Finding Most Efficient Algorithm for Segregating and Saving Data: A Comparative Analysis - Vyas, Heli P; Shah, Sanjay M (International Journal of Computer Sciences and Engineering, 2025)
Data mining is the process of making patterns for large data sets. There are many data mining algorithms proposed in recent years. All algorithms work on different data type so one algorithm may not be used for all applications. On the basis of requirement and compatibility of dataset, an algorithm will be applied. Apriori is a classical algorithm which is use for all dataset. But there are some shortfalls of Apriori algorithm. Our, proposed Data segregation algorithm is introduced to address the effect of these short comings of apriori. The comparison of two algorithm studied on the basis of some criteria discussed in the paper.